Romantic Elements in Laxmiprasad Devkota’s Muna-Madan - Thapa, Dharma Bahadur (Tribhuvan University Journal, 2020)
This article is an attempt to study Laxmiprasad Deckota’s poetic work Muna-Madan to see how much it concords the romantic philosophical parameters. It analyses the textual properties of the work on the basis of romantic principles and philosophy propounded by William Wordsworth in his famous essay “Preface to Lyrical Ballads.” It also invokes C. W. F. Von Schlegel’s poetic theory and the philosophically grounded definitions of romanticism given by authors like Bertrand Russell, Justin and Gaarder. Finally the paper comes to the conclusion that Devkota’s Muna-Madan contains all the major characteristics like strong subjectivism, foregrounding of folk culture, privileging the common over the sophisticated and spiritualization of nature that a romantic poetry should possess.